Analysis of circular population migration pattern from Sigi Regency to Palu City - Hadi Suryono; Iwan Alim Saputra (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2022)
Urbanization is closely related to regional development. The population migration in Palu City is mostly caused by the people’s needs to fulfill their needs. This study aims to identify the migration pattern of the residents of Sigi Regency to Palu City. This study used a descriptive quantitative method and gathered data from secondary data on the Labor Force (AK) from the Center Bureau of Statistics of Palu City in 2015 and 2019. Meanwhile, the data analysis was carried out using gravity analysis to see the interactions and linkages between Palu City and Sigi Regency. Our data analysis results indicate that the migration pattern of the non-permanent population in Palu City was daily, weekly and monthly pattern and dominated by circular migration. Based on the gravity analysis, as a center of development, Palu City has an intensive and close interaction with Sigi Regency. Factors that influence this pattern of migration are accessibility, distance, facilities, and infrastructure. Meanwhile, population and the amount of regional income are the reasons for the interaction between regions. This research can be used as a reference in the learning related to urban village Geography.